2020
DOI: 10.14245/ns.1938454.227
|View full text |Cite
|
Sign up to set email alerts
|

Telerobotic Spinal Surgery Based on 5G Network: The First 12 Cases

Abstract: The purpose of this study was to determine the efficacy and feasibility of 5th generation wireless systems (5G) telerobotic spinal surgery in our first 12 cases. Methods: A total of 12 patients (5 males, 7 females; age, 23-71 years) with spinal disorders (4 thoracolumbar fractures, 6 lumbar spondylolisthesis, 2 lumbar stenosis) were treated with 5G telerobotic spinal surgery. Sixty-two pedicle screws were implanted. Results: All patients had substantial relief from their symptoms. Screw placements were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 33 publications
0
84
0
Order By: Relevance
“…Five, minimal data are available on telesurgery and telementoring for urological procedures [10]. The surgical literature is indeed larger, and some applications of telementoring and telesurgery have been reported [57], including, very recently, even 5G telerobotic spinal surgery [58]. Likely, we will witness a similar development also for the urological surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Five, minimal data are available on telesurgery and telementoring for urological procedures [10]. The surgical literature is indeed larger, and some applications of telementoring and telesurgery have been reported [57], including, very recently, even 5G telerobotic spinal surgery [58]. Likely, we will witness a similar development also for the urological surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can never avoid the development of bone grinding arms in the development of spinal surgery robots. This research advances the development of a safe cortical bone treatment technique that never damages nerves as a program by linking tissue characteristics with precise position information and linking information obtained from sensors such as drill vibrations with position information [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A last aspect for the future is the extension of telemedicine service to include surgical interventions. Tian et al [ 17 ] recently published their experience with telerobotic spinal surgery based on 5G technology. They performed remote surgery in 12 cases and concluded that this technology could build a connection between surgeons and patients located in isolated or rural areas with a lack of medical resources.…”
Section: Discussionmentioning
confidence: 99%